Bibliometric Analysis of Reflective Practices in Physics Learning: Trends, Challenges, and Future Directions - Hanan Zaki Alhusni; Binar Kurnia Prahani; Titin Sunarti; Madlazim Madlazim (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2025)
Objective: This study aims to provide a comprehensive bibliometric analysis of reflective practices in physics education, identifying global trends, research gaps, and future directions. The focus is to map the development of reflective practices as a key 21st-century skill in physics learning and to highlight their role in strengthening conceptual understanding, metacognitive awareness, and student autonomy. Method: A bibliometric research design was employed using the Scopus database as the primary source. Data were collected from 1995 to 2025, filtered according to inclusion criteria, and analyzed using performance analysis and science-mapping techniques. Tools such as VOSviewer and Biblioshiny were used to visualize publication trends, collaboration networks, and keyword co-occurrences, ensuring validity and replicability. Results: The findings indicate significant growth in publications since 2015, peaking in 2024. Conference proceedings dominate research outputs, while reputable journals play a more minor yet influential role. The United States, China, and Indonesia emerge as leading contributors, with varying levels of international collaboration. Keyword analysis highlights